Examining the Effectiveness of an Educational-Therapeutic Package Based on the Perception of Women’s Lived Experiences During Divorce on Suffering in Bajestan - Azghandi Shahri, Majid; Fallah, Mohamad Hussein; Vaziri, Saeed (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to examine the effectiveness of an educational-therapeutic package based on the perception of women’s lived experiences during divorce on suffering in Bajestan. Methods and Materials: This research employed a quasi-experimental design with a pre-test and post-test and a control group. The statistical population included all women undergoing divorce in Bajestan in 2022. Through purposive sampling, 30 women were selected and randomly assigned to experimental and control groups. The data collection instrument was the scale developed by Schaalz et al. (2010). Data analysis was conducted using descriptive statistics (mean, standard deviation) and inferential statistics (covariance analysis). Findings: The findings indicated that the educational-therapeutic package based on women’s lived experiences during divorce effectively reduced their suffering. Additionally, this intervention assisted them in approaching the topic of divorce rationally, free from excessive emotions, and increased their willingness to seek counseling. Conclusion: Based on the study’s findings, it can be concluded that the proposed educational-therapeutic package can be used as an appropriate intervention tool to reduce suffering among women undergoing divorce.